The Doctors Book of Home Remedies for Women: Women Doctors Reveal 2,000 Self-Help Tips on the Health Problems That Concern Women the Most - Edited by Faelten, Sharon (Emmaus, Pa Rodale Press, 1997)
In the tradition of the best-selling 10-million-copy Doctors Book of Home Remedies, this is the first book to focus exclusively on home remedies from women doctors, for the women they counsel.
Includes Index.
Keywords: Women -- Health and hygiene